Fostering green innovation adoption through green dynamic capability: the moderating role of environmental dynamism and big data analytic capability - Yu, Danni; Tao, Shen; Abdul Hanan; Ong, Tze San; Latif, Badar; Ali, Mohsin (Multidisciplinary Digital Publishing Institute, 2022)
Though the concept of green dynamic capability has been increasingly gaining traction among academics, practitioners, and policymakers, its association with green innovation adoption remains unclear. The present study addresses this gap and aims to provide clarity by distinguishing green innovation adoption in the context of developing countries. Drawing on dynamic capability and stakeholder theory, this research shed light on the significance of green dynamic capability for green innovation adoption. Additionally, this study examines the moderating role of environmental dynamism and big data analytics capability in the link between green dynamic capability and green innovation adoption. Adopting a two-wave research design, the sample for this study contained SMEs from Pakistan and Malaysia. Data was obtained from 220 SMEs (105 from Pakistan, 115 from Malaysia). To test the hypotheses, covariance-based structural equation modelling was performed to analyze causal relationships in the model, by using AMOS 23 software. The results showed that green dynamic capability positively impacts green innovation adoption, but environmental dynamism does not positively moderate between green dynamic capability and green innovation adoption. In addition, big data analytics capability positively moderates between green dynamic capability and green innovation adoption. We believe that this study opens a new avenue in the environmental literature under which green innovation adoption is useful for SMEs.